2016
DOI: 10.21093/ijeltal.v1i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Vocabulary Mastery through TPR Storytelling

Abstract: Teaching English for primary school students highly emphasizes on vocabulary. It is understandable since they are at the first stage of learning the language. Unfortunately, in many teaching practices, vocabulary is taught in an isolated way without the presence of meaningful context. Vocabularies are often given in the form of long list to be memorized. Actually, the aim of learning vocabulary is to equip the students to be ready to use the language (i.e. speaking). Therefore, here, Total Physical Response St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Türkeş (2011) stated that the fifth grade students gradually started to like the TPRS method due to stories, had fun during the lesson, found the topics covered in the lesson easy and learned new things. Nuraeningsih and Rusiana (2016) determined that the TPRS method improved vocabulary skills of second grade students, and all students had fun and were happy, and the TPRS method was a new, exciting experience for students. Examining the views of students on the G-T method, Griffiths (2008) found that the preferences of higher-level language students regarding learning methods were eclectic, and they preferred many other methods instead of methods that only emphasize grammar, translation or vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…Türkeş (2011) stated that the fifth grade students gradually started to like the TPRS method due to stories, had fun during the lesson, found the topics covered in the lesson easy and learned new things. Nuraeningsih and Rusiana (2016) determined that the TPRS method improved vocabulary skills of second grade students, and all students had fun and were happy, and the TPRS method was a new, exciting experience for students. Examining the views of students on the G-T method, Griffiths (2008) found that the preferences of higher-level language students regarding learning methods were eclectic, and they preferred many other methods instead of methods that only emphasize grammar, translation or vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…English receptive skills are essential for primary school pupils because they create the groundwork for efficient communication and comprehension of spoken and written language. English receptive skills for primary pupils refer to the ability to understand and comprehend English language (Nuraeningsih, 2022). These skills include listening and reading comprehension, which are essential for effective communication and language learning.…”
Section: English Receptive Skills For Primary Pupilsmentioning
confidence: 99%
“…Moreover, in order to be able to express ideas and understand others, an adequate vocabulary is needed because it is the basis of learning foreign language (Kuśnierek, 43 C.E. ;Nuraeningsih, N. & Rusiana, 2016). A language learner cannot communicate effectively without knowing enough vocabulary (Bahrami et al, 2019).…”
Section: The Important Of Mastering English Vocabularymentioning
confidence: 99%